THE IMPACT OF COVID-19 PANDEMIC ON INDONESIAN AEROSPACE (IAE) BUSINESS PROCESS - Mohamad Ikhsan Nurulloh; Luhut Simbolon; George Royke Deksino (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
The purpose of this study is to provide an overview of the impacts of the Covid-19 pandemic on the value chain in the IAe business process. The Covid-19 pandemic encourages IAe to preserve and improve its business processes. Identifying issues along the value chain could provide information about the effects of Covid-19 on the IAe business process. IAe should overview the condition of the value chain affected by the Covid-19 pandemic to evaluate its business process and utilize it as a basis for future improvements. According to the study's findings, the Covid-19 pandemic has a negative impact on the value chain activities, both primary and supporting activities, throughout the IAe business process. The organization must make continuous improvements to leverage post-pandemic opportunities by designing strategies based on the recovery plan.